PEMBUATAN MIKROENKAPSULASI DENGAN BAHAN PEREMAJA MINYAK TANAH DAN SOLAR - , AJENG PUTRI MAHARANI; , Ir. Heru Budi Utomo, MT. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Minor road damage such as surfaces crack must be treated immediately to prevent damage the roads become more complex. Surface cracks shorten the service life of the road and itâs adverse consequence. In general, roads damage caused by lack of proper planning, poor supervision, lack of road maintenance costs, delay spending budget causes delays handling damage, and improper handling priority. The consequence was road repairs should be done immediately and require a great expense. Self-healing materials are materials to prevent premature damage to road construction that can repair itself suffered damage by implanting microencapsulated fluxing material containing asphalt in asphalt concrete mixtures. Microencapsulation is composed of a core made from pumice, self healing fluxing agent in the form of asphalt materials (kerosene and diesel), and the walls are made of cement and epoxy. If there is a crack, a crack propagates and reach and damage the walls of microencapsulation. Fluxing material in microencapsulation flow and then close the cracks. Closing loopholes and restore the integrity of the material ability to prevent the degradation of structural materials. Microencapsule are made to replace fraction of fine aggregate in asphalt concrete. Specific gravity of the test showed that the self-healing microencapsulation agent kerosene and diesel measuring 2 mm has a specific gravity 2.092